1985
DOI: 10.1007/bf01799652
|View full text |Cite
|
Sign up to set email alerts
|

3‐Hydroxy‐3‐methylglutaryl‐coenzyme A lyase deficiency: A review

Abstract: Children with 3-hydroxy-3-methylglutaryl-CoA lyase deficiency (HMG-CoA-LD; McKusick 24645), have inherited two areas of metabolic weakness. Firstly, they are unable to metabolize fully the carbon skeleton of leucine, and secondly, they cannot make ketone bodies in response to prolonged fasting. In the first year of life infants with HMG-CoA-LD run a high risk of developing severe hypoglycaemia which can lead to death if prompt intervention does not occur. The metabolic crisis develops when the infant is first … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0
3

Year Published

1987
1987
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 30 publications
1
46
0
3
Order By: Relevance
“…To date we have diagnosed 7 cases. Patients present with in termittent attacks of severe nonketotic hypo glycemia under conditions of prolonged fast ing [29]. Our experience with this disorder showed that a fair number of patients died in childhood; we also observed permanent brain damage following an attack.…”
Section: Resultsmentioning
confidence: 64%
“…To date we have diagnosed 7 cases. Patients present with in termittent attacks of severe nonketotic hypo glycemia under conditions of prolonged fast ing [29]. Our experience with this disorder showed that a fair number of patients died in childhood; we also observed permanent brain damage following an attack.…”
Section: Resultsmentioning
confidence: 64%
“…(Schutgens et al, 1979;Gibson et al, 1988a;Gibson et al, 1988b). In some cases the progresive lowered state of consciousness leads to coma and subsequent death (Wysocki et al, 1986). Laboratory data that stand out are the metabolic acidosis and non-ketotic hypoglycemia (Table 1).…”
Section: Acute Crisismentioning
confidence: 99%
“…In the latter, most of the patients show muscular weakness and myopathy (Ribes et al, 2003). In the HL deficiency symptoms as dehydration, hypotonia, hypothermia, tachypnea, lethargy, coma and even death, have been reported (Wysocki & Hahnel, 1986;Menao et al, 2009). Up to date, no patient with mHS deficiency has died due to this disease.…”
Section: Differential Diagnosis With Hmg-coa Lyase Deficiencymentioning
confidence: 99%